Research design quantitative, qualitative, mixed methods, arts-based, and community-based participatory research approaches - Leavy, Patricia 1975- (New York Guilford Press, 2017)
This user-friendly book provides a step-by-step guide to using the five major approaches to research design: quantitative, qualitative, mixed methods, arts-based, and community-based participatory research. Chapters on each approach follow a unique format--they present a template for a research proposal and explain in detail how to conceptualize and fill in every section. Terminology commonly used within each approach is identified, and key moments of ethical decision making are flagged. Interdisciplinary research examples draw on current events and social justice topics.
Part I: The nuts and bolts of research design: Introduction to social research -- Ethics in social research -- Getting started designing a project -- Part II: Five approaches to research design: Quantitative research design -- Qualitative research design -- Mixed methods research design -- Arts-based research Design -- Community-based participatory research design.
Includes bibliographical references (pages 273-286) and indexes.
Keywords: Social sciences -- Research -- Methodology; Interdisciplinary research -- Methodology; Quantitative research -- Methodology; Qualitative research -- Methodology